Bridging the digital divide from the grassroots: The social and economic impact of RT/RW Net in Jabodetabek Urban Periphery - Hendra Gilbert; Prio Utomo; Krist Ade Sudiyono (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
Despite high internet penetration rates, the benefits of digitalization remain unevenly distributed in Indonesia’s densely populated urban areas. This study investigates RT/RW Net, a community-driven internet network that has emerged as a grassroots response to the digital divide in Jabodetabek. While often viewed primarily through a legal or technical lens, the socio-economic implications of these networks remain under-explored. Using an interpretive phenomenological approach, this study analyzes data from in-depth interviews, observations, and document analysis involving network managers, users, and local community leaders. The findings reveal that residents adopt RT/RW Net primarily due to affordability and flexible payment schemes. Beyond connectivity, these networks function as mechanisms for Community Driven Digital Inclusion (CDDI), fostering social cohesion through